Schizotypal Traits are Linked to Dopamine-Induced Striato-Cortical Decoupling: A Randomized Double-Blind Placebo-Controlled Study. (7th June 2018) - Rössler, Julian; Unterassner, Lui; Wyss, Thomas; Haker, Helene; Brugger, Peter; Rössler, Wulf; Wotruba, Diana
Abstract: The dopamine hypothesis of schizophrenia implies that alterations in the dopamine system cause functional abnormalities in the brain that may converge to aberrant salience attribution and eventually lead to psychosis. Indeed, widespread brain disconnectivity across the psychotic spectrum has been revealed by resting-state functional magnetic resonance imaging (rs-fMRI). However, the dopaminergic involvement in intrinsic functional connectivity (iFC) and its putative relationship to the development of psychotic spectrum disorders remains partly unclear—in particular at the low-end of the psychosis continuum. Therefore, we investigated dopamine-induced changes in striatal iFC and their modulation by psychometrically assessed schizotypy. Our randomized, double-blind placebo-controlled study design included 54 healthy, right-handed male participants. Each participant was assessed with the Schizotypal Personality Questionnaire (SPQ) and underwent 10 minutes of rs-fMRI scanning. Participants then received either a placebo or 200 mg of L-DOPA, a dopamine precursor. We analyzed iFC of 6 striatal seeds that are known to evoke modulation of dopamine-related networks. The main effect of L-DOPA was a significant functional decoupling from the right ventral caudate to both occipital fusiform gyri. This dopamine-induced decoupling emerged primarily in participants with low SPQ scores, while participants with high positive SPQ scores showed decoupling indifferently of the L-DOPA challenge. Taken together, these findings demonstrate that schizotypal traits may be the result of dopamine-induced striato-occipital decoupling.